Humanismo e emancipação na ética normativa de Frantz Fanon - Siqueira, Lucas Teixeira (My University, 2023)
This document intends to discuss the work of Frantz Fanon (1925-1961), in order to investigate the possibilities of conceptual and practical updates referring to the context examined by the author. From the question: "Is it possible to define a philosophy of action and, therefore, an ethics based on the concepts of humanism and emancipation in the work of Frantz Fanon?", it is intended to delimit his applications and propositions in line with the present reality. Our work focuses on the analysis of the book "Os Condenados da Terra" (1961), but will also seek support from commentators and works of similar thematic and critical exercise. Our objective will be to interpret the fanonians themes seeking an update and possible applicability to the contemporary context. The intended diagnosis of a philosophy of action related to the concept of radical humanism and emancipatory praxis will also be the result of an approximate dialogue between Frantz Fanon's thought and Enrique Dussel's theory of liberation. [resumo fornecido pelo autor]
Este trabalho pretende dissertar sobre a obra de Frantz Fanon (1925-1961), a fim de investigar as possibilidades de atualizações conceituais e práticas referentes ao contexto examinado pelo autor. A partir da questão: "É possível definir uma filosofia da ação e, por conseguinte, uma ética tendo por base os conceitos de humanismo e emancipação na obra de Frantz Fanon?", pretende-se delimitar suas aplicações e proposições em consonância com a realidade presente. Nosso trabalho concentra-se na análise da obra "Os Condenados da Terra" (1961), mas também buscará apoio em comentadores e obras de temática e exercício crítico semelhantes. Nosso objetivo será o de interpretar os temas fanonianos buscando uma atualização e possível aplicabilidade ao contexto contemporâneo. O diagnóstico pretendido de uma filosofia da ação referida ao conceito de humanismo radical e à práxis emancipatória será também o resultado de um diálogo aproximativo entre o pensamento de Frantz Fanon e a teoria da libertação de Enrique Dussel. [resumo fornecido pelo autor]
Keywords: Fanon, Frantz, 1925-1961; Dialética; Ética; Humanismo; Filosofia; Dialectic; Ethics; Humanism; Philosophy